The pathfinder, or, The inland sea - Cooper, James Fenimore, 1789-1851 (State University of New York Press, 1981)
In the sequel to The Last of the Mohicans, Natty Bumppo tries to help a small outpost on Lake Ontario.
Keywords: Bumppo, Natty -- (Fictitious character); Bumppo, Natty (Fictitious character) -- Fiction.; United States -- History -- French and Indian War, 1754-1763 -- Fiction.; États-Unis -- Histoire -- 1755-1763 (Guerre de Sept Ans) -- Romans, nouvelles, etc.; États-Unis -- Histoire -- 1754-1763 (Guerre de Sept Ans) -- Romans, nouvelles, etc.; FICTION -- Historical.; United States; 1754-1763; United States -- History -- French and Indian War, 1755-1763 -- Fiction; War stories.; War stories; Historical fiction; Fiction; History; Historical fiction.; Novels.